Hubungan antara Kemampuan Seni Rupa dengan Minat Mengajarkan Kerajinan Tangan dan Kesenian Mahasiswa PGSD - Amir Amir; Nasaruddin Nasaruddin (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
The focus of this research is to test wether there is a significant correlation between art knowledge and interest in teaching arts. Two hundred students of primary school teacher education at State University of Makassar were involved. The descriptive analysis of the data obtained from documentation and questionnaire indicates that there was a positive correlation between the students’ knowledge and their interest in teaching arts in primary schools.